Imagining the Image: A Reflection on Visual Features of Literary Imagery - Zoheir Nadalizadeh (مطالعات زبانی و بلاغی)
In both Persian and Arabic rhetorical traditions, the classification and analysis of tropes and poetic imagery is swarming with nuances and novel findings. Among them, simile and metaphor, on which several monographs have been written, would especially stand out. But such scrutiny into details has at times prevented scholars from considering those questions which come to be more broadly conceived. One such query, rarely found in our rhetorical tradition, pertains to the essential nexus between the modes of expression, on the one hand, and the image and the literary imagery, on the other. The present analytical-descriptive research examines this question, referring to some predominantly Western theories, in an attempt to demonstrate how the use of the term “image” can be misleading with regard to modes of expression and its functions. An image can sometimes assume the capability of evoking mental associations, but it might never take on visual qualities and thus can hardly be imagined. Poetic images are not perceived through sensory perceptions or visualizations, but instead via a series of mental processes aimed at their rational interpretation. With that in mind, we will briefly look into those types of verbal imagery whose main purpose is not the expression of an emotional experience or image-making, but rather producing implicit significations by the use of puns, parallelisms, ambiguities and allusions.